Analysis of curriculum development and accounting learning at SMK Indonesia Raya - Alivia Alviasari; Ine Azizah; Monicha Dewi Anggraeni; Muhamad Mario Darpa (Hipkin Journal of Educational Research, 2025)
The development of the accounting curriculum in Vocational High Schools (SMK) is essential in preparing graduates who are ready to compete in the world of work. However, the dualism of implementing the Kurikulum 2013 and the Kurikulum Kerdeka poses a challenge for schools in adjusting the curriculum to the ever-growing industry's needs. A curriculum not in line with industry standards can hinder students' readiness to face the world of work. This study aims to evaluate the implementation of the accounting curriculum at SMK Indonesia Raya and identify its challenges and opportunities. The method used is qualitative, with observation and in-depth interviews with teachers, students, and school management. Data analysis was carried out descriptively to understand the effectiveness of the curriculum implemented. The study results show that the dualism of the curriculum causes differences in learning strategies, teacher readiness, and student understanding of industry-based materials. The Kurikulum Merdeka provides more flexibility, but limited infrastructure and readiness of teaching staff are the main obstacles. In conclusion, the development of accounting curriculum in SMK requires synergy between the government, schools, and industry to ensure relevance to the job market. With an adaptive curriculum, competent teaching staff, and adequate facilities, SMK graduates can be highly competitive in the era of globalization.   Abstrak Pengembangan kurikulum akuntansi di Sekolah Menengah Kejuruan (SMK) berperan penting dalam mempersiapkan lulusan yang siap bersaing di dunia kerja. Namun, dualisme penerapan Kurikulum 2013 dan Kurikulum Merdeka menimbulkan tantangan bagi sekolah dalam menyesuaikan kurikulum dengan kebutuhan industri yang terus berkembang. Kurikulum yang tidak selaras dengan standar industri dapat menghambat kesiapan peserta didik dalam menghadapi dunia kerja.Penelitian ini bertujuan mengevaluasi implementasi kurikulum akuntansi di SMK Indonesia Raya serta mengidentifikasi tantangan dan peluangnya. Metode yang digunakan adalah pendekatan kualitatif dengan observasi dan wawancara mendalam terhadap pendidik, peserta didik, serta manajemen sekolah. Analisis data dilakukan secara deskriptif untuk memahami efektivitas kurikulum yang diterapkan. Hasil penelitian menunjukkan bahwa dualisme kurikulum menyebabkan perbedaan strategi pembelajaran, kesiapan pendidik, serta pemahaman peserta didik terhadap materi berbasis industri. Kurikulum Merdeka memberikan fleksibilitas lebih, tetapi keterbatasan infrastruktur dan kesiapan tenaga pengajar menjadi kendala utama.Kesimpulannya, pengembangan kurikulum akuntansi di SMK membutuhkan sinergi antara pemerintah, sekolah, dan industri untuk memastikan relevansi dengan pasar kerja. Dengan kurikulum adaptif, tenaga pendidik kompeten, serta fasilitas memadai, lulusan SMK dapat memiliki daya saing tinggi di era globalisasi. Kata Kunci: kurikulum sekolah menengah kejuruan; pembelajaran akuntansi; pengembangan kurikulum